A pancreaticoduodenal artery aneurysm. (15th June 2015) - Lewis, Jason Robert; Refson, Jonathan Simon
Abstract : A 70-year-old man was investigated with CT imaging for haematuria. An incidental finding was made of a large inferior pancreaticoduodenal artery aneurysm. Following a period of monitoring, the patient underwent open repair of the aneurysm. This case report highlights an unusual pathology and discusses the clinical complexities related to its management.